Scenario simulation of ecological risk based on land use/cover change – A case study of the Jinghe county, China - Yue Zhang (Elsevier, 2021)
The Jinghe County of the Ebinur Lake Basin was chosen as the study area. Based on Landsat TM / OLI images obtained in 2007 and 2017, this paper attempts to use CLUE-S model to predict LUCC under three different scenarios (Natural Development scenario, Farmland Protection scenario, Water Resources Protection scenarios) in 2027. Landscape indices and ecological risk index were calculated and spatially interpolated for the whole region, and the results of ecological risk could be divided into five different zones: extremely low, low, moderate, high and extremely high. They were carried out for assessing the spatial–temporal changes in ecological risk for each landscape pattern. The results show that: (1) Among the three scenarios designed in this paper, the spatial distribution of LUCC in the Water Resource Protection scenario has the most obvious changes, followed by the Farmland Protection scenario and the Natural Development scenario becomes the third. In the water resources protection scenario, the scale of the desert decreases, but the forest and grass part increases, which is conducive to ecological improvement. (2) the distribution area of high ecological risk areas was the largest of three different scenarios, especially the farmland protection scenario. The area of low-risk level is the largest under the water conservation scenario. The ecological risk of LUCC under the water resources protection scenario is lower, which is better for ecological environment. (3) Water bodies mainly concentrate upon low ecological risk degree, accounting for approximately 62.8%, 82.2%, and 73.1% of low ecological risk; Farmland mainly lies in the low-risk areas, accounting for 59.1%, 63.5% and 68.8% of the lower ecological risk levels; In 2027, the unused land and other land types are the main land types of the higher ecological risk areas under three different scenarios, whose proportions are 67.40%, 68.24% and 65.90%, respectively.